2022
DOI: 10.1371/journal.pone.0268220
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of information provided within degenerative cervical myelopathy education resources: Towards enhancing shared decision making

Abstract: Background Degenerative cervical myelopathy (DCM) is a chronic neurological condition estimated to affect 1 in 50 adults. Due to its diverse impact, trajectory and management options, patient-centred care and shared decision making are essential. In this scoping review, we aim to explore whether information needs in DCM are currently being met in available DCM educational resources. This forms part of a larger Myelopathy.org project to promote shared decision making in DCM. Methods A search was completed enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Few studies have assessed the quality of DCM information available to the public. 19,20 Patient awareness and education of the condition are generally lacking, and there is a paucity of trustworthy sources available outside of the clinical setting. 21 One study found that information on DCM across various media largely pertained to health professionals, with only 15% targeted toward patients or layperson.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have assessed the quality of DCM information available to the public. 19,20 Patient awareness and education of the condition are generally lacking, and there is a paucity of trustworthy sources available outside of the clinical setting. 21 One study found that information on DCM across various media largely pertained to health professionals, with only 15% targeted toward patients or layperson.…”
Section: Discussionmentioning
confidence: 99%
“…21 One study found that information on DCM across various media largely pertained to health professionals, with only 15% targeted toward patients or layperson. 19 Another study on DCM and social media ( Twitter. com) reported that less than a third of tweets focused on spreading awareness and information.…”
Section: Discussionmentioning
confidence: 99%
“…Narrative reviews were selected because narrative reviews typically aim to provide educational content, and systematic reviews focus on specific clinical questions [ 20 , 21 ]. This methodology was formulated from a previously published scoping review on educational resources in degenerative cervical myelopathy- this confirmed most systematic reviews examined a clinical research question rather than provide educational content [ 22 ]. To consider an information bias (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For website-based resources, a hierarchical search strategy was employed to identify CSDH educational content with sequential searching of identified websites using page navigation, site search facilities, and finally in-page searching for the term ‘Chronic Subdural Haematoma’. Websites were chosen based on their popularity as a health information resource, as defined in a previous review [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…“What can I expect—When will I recover?” Frequent questions in those undergoing surgery for degenerative cervical myelopathy (DCM). 1a,2a…”
Section: Commentsmentioning
confidence: 99%